The Role of Job Characteristics in Enhancing Work Engagement and Reducing Burnout: An Empirical Study on Indonesian Migrant Workers in Taiwan - Pramono, Galih; Purwaningrum, Dyah (International Business Management - Universitas Ciputra, 2025)
Burnout has become an increasingly prevalent issue among employees facing high work demands, often manifesting as emotional exhaustion, cynicism, and declining job performance. This study aims to explore the impact of job characteristics on burnout, emphasizing the mediating role of work engagement. The research examines explicitly Indonesian migrant workers in Taiwan, a group that frequently encounters unique occupational challenges and stressors. A quantitative method was adopted, utilizing a survey method with 139 respondents selected through purposive sampling. Data were gathered through structured questionnaires and analyzed using path analysis to assess the interrelationships among key variables. The results reveal that positive job characteristics strengthen work engagement, including autonomy, task significance, job variety, and feedback. Moreover, work engagement is identified as a significant mediator, illustrating that employees who experience favorable job conditions tend to exhibit higher levels of engagement, which in turn mitigates burnout. The findings of this study underscore the importance of strategic job design in promoting employee well-being, particularly for migrant workers who are more vulnerable to excessive work pressures. By fostering supportive job characteristics, organizations can enhance engagement levels and create a work environment that minimizes burnout.